Impact of Laser Speed and Drug Particle Size on Selective Laser Sintering 3D Printing of Amorphous Solid Dispersions - Rishi Thakkar; Miguel O. Jara; Steve Swinnea; Amit R. Pillai; Mohammed Maniruzzaman (MDPI AG, 2021)
This research demonstrates the influence of laser speed and the drug particle size on the manufacturing of amorphous solid dispersions (ASD) and dosage forms thereof using selective laser sintering 3-dimensional (3D) printing. One-step manufacturing of ASD is possible using selective laser sintering 3D printing processes, however, the mechanism of ASD formation by this process is not completely understood and it requires further investigation. We hypothesize that the mechanism of ASD formation is the diffusion and dissolution of the drug in the polymeric carrier during the selective laser sintering (SLS) process and the drug particle size plays a critical role in the formation of said ASDs as there is no mixing involved in the sintering process. Herein, indomethacin was used as a model drug and introduced into the feedstock (Kollidon® VA64 and Candurin® blend) as either unprocessed drug crystals (particle size > 50 µm) or processed hot-melt extruded granules (DosePlus) with reduced drug particle size (<5 µm). These feedstocks were processed at 50, 75, and 100 mm/s scan speed using SLS 3D printing process. Characterization and performance testing were conducted on these tablets which revealed the amorphous conversion of the drug. Both MANOVA and ANOVA analyses depicted that the laser speed and drug particle size significantly impact the drug's apparent solubility and drug release. This significant difference in performance between formulations is attributed to the difference in the extent of dissolution of the drug in the polymeric matrix, leading to residual crystallinity, which is detrimental to ASD's performance. These results demonstrate the influence of drug particle size on solid-state and performance of 3D printed solid dispersions, and, hence, provide a better understanding of the mechanism and limitations of SLS 3D printing of ASDs and its dosage forms.